2018
DOI: 10.1080/10810730.2018.1511013
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of E-Government Applications for Public Health Risk Communication: Government Trust and Social Media Competence as Primary Drivers

Abstract: Building upon a framework of the unified theory of acceptance and use of technology, this study explores the determinants of citizens' intentions to use the government's mobile application for public health risk communication. An online survey was conducted with a quota sample of 700 Korean citizens. The results from structural equation modeling suggest that social media competence and trust in government information are primary determinants of willingness to accept the new application and intention to use it.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(68 citation statements)
references
References 40 publications
5
54
0
8
Order By: Relevance
“…Thus, the following is hypothesized: Risk perception may also be significant as a predictor of usage intention (Fischer et al, 2019). This finding is supported by prior research done by H. Park and Lee (2018), which showed that risk perception, directly and indirectly, influenced one's intention to use an application for risk communication purposes and that risk-related perceptions (including perceived severity, perceived susceptibility, and response efficacy) are antecedents of riskrelated information-seeking behavior and subsequently influence whether an individual accepts a new app for risk management developed by the government. Hence: H13: Risk perception will have a significant influence on the intention to use SIKK Magelang.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 73%
See 2 more Smart Citations
“…Thus, the following is hypothesized: Risk perception may also be significant as a predictor of usage intention (Fischer et al, 2019). This finding is supported by prior research done by H. Park and Lee (2018), which showed that risk perception, directly and indirectly, influenced one's intention to use an application for risk communication purposes and that risk-related perceptions (including perceived severity, perceived susceptibility, and response efficacy) are antecedents of riskrelated information-seeking behavior and subsequently influence whether an individual accepts a new app for risk management developed by the government. Hence: H13: Risk perception will have a significant influence on the intention to use SIKK Magelang.…”
Section: Literature Review and Hypotheses Developmentsupporting
confidence: 73%
“…Risk and hazard communication aim to inform people of potential dangers, predictions of future events, and technical information regarding how dangerous risks could be and what to do if they occur (Rogers, 2020). Social media and other new communication technologies, along with location-based services, now facilitate the rapid delivery of information, real-time interaction, and place-based knowledge generation (H. Park & Lee, 2018;Thomas, 2018). Accordingly, governments (including governments at the local level) are working towards developing apps specifically for disaster-management purposes or dissemination of information of disasters to the public.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 31 2019 E-business evolution: an analysis of mobile applications' business models Technology Analysis and Strategic Management Cristofaro, M. 32 2018 The effects of human-game interaction, network externalities, and motivations on players' use of mobile casual games Industrial Management and Data Systems Molinillo, S., Muñoz-Leiva, F., Pérez-García, F. 33 2018 Acceptance and usage of a mobile information system services in University of Jordan Education and Information Technologies Almaiah, M.A. 34 2018 Adoption of E-Government Applications for Public Health Risk Communication: Government Trust and Social Media Competence as Primary Drivers Journal of Health Communication Park, H., Lee, T.D. 35 2018 Evaluating Consumers' Adoption of Mobile Technology for Grocery Shopping: An Application of Technology Acceptance Model Vision Shukla, A., Sharma, S.K.…”
Section: Methodsmentioning
confidence: 99%
“…Effective communication can create public trust in the government, which, in turn, encourages information sharing and mutual cooperation between ministries and organizations in charge of the disaster. 8 Public service advertising is one of the main methods that a government uses to communicate with the public, and one of its primary goals is to enhance public awareness of vital social issues. 9 Consequently, public service advertisements (PSAs) serve as tools of persuasion to convince the public to change their beliefs, attitudes, and behaviors.…”
Section: Introductionmentioning
confidence: 99%